On the efficiency criteria of work practices with ASD people - Morozov S.A (Moscow State University of Psychology and Education, 2017)
The analysis of different practices of work with ASD people has important application value. First of all, it aims to identify the effectiveness of various factors and their combination on the development of people with autism, and on the level of their social adaptation. The question of the effectiveness of correction of ASD is considered both in terms of the choice of techniques and practices for work with ASD children, and in terms of the effectiveness of techniques as such and the content of «effectiveness of correction of ASD» concept. The most competent of the modern approaches to the evaluation of the effectiveness of the techniques and the practice of correction of autistic disorders, the prospects and directions of research of this indicator are determined.